Efficacy and acceptability of psilocybin for primary or secondary depression: A systematic review and meta-analysis of randomized controlled trials - Fang, Shuping; Yang, Xin; Zhang, Wei (Frontiers in Psychiatry, 2024)
Psilocybin is a classic psychedelics, which has been shown to have antidepressant effects by many studies in recent years. In this study, we aim to evaluate the efficacy, acceptability and tolerability of psilocybin in the treatment of primary (major depressive disorder) or secondary (experiencing distress related to life-threatening diagnoses and terminal illness) depression. Methods: We searched PubMed, EMBASE, Web of Science, Cochrane Library and ClinicalTrials.gov for clinical trials of psilocybin for depression (updated to 4 October, 2023). Effect size Hedges' g was used as an indicator of efficacy, and other outcomes included response rate, drop-out rate, and adverse events. Results: A total of 10 studies were finally included in systematic review. 8 studies were included in the meta-analysis, involving a total of 524 adult patients, and produced a large effect size in favor of psilocybin (Hedge's g =-0.89, 95% CI -1.25~-0.53, I² = 70.19%, P<0.01). The therapeutic effects of psilocybin increase with increasing doses. Adverse events caused by psilocybin are generally transient and reversible, but serious adverse events also may occur. Discussion: Our study shows that psilocybin has both short-term and long-term antidepressant effects and holds promise as a potential complementary or alternative therapy for depression, probably. Further research may reveal more about its therapeutic potential.